Update of INR-selfmonitoring - Völler, H; Braun, S (Hämostaseologie, 2008)
Nearly every second patient, who needs an oral anticoagulation with vitamin K antagonists, is feasible to perform INR-self-management after participation in a structured teaching program. Patient self-testing or measuring the INR value by relatives or nurses would increase this method of control by the aid of telemedicine systems. An accurately, weekly measurement leads to an optimal therapeutic control of anticoagulation intensity, which results in an impressive risk reduction up to 50%. This depends not on the underlying heart disease and had been demonstrated in patients older than 60 years. Due to the small INR variability and therefore a higher percentage in target range, a lower anticoagulation intensity in patients with mechanical heart valve prosthesis should be justifiable. For the next decade, INR self-management/self-testing should be the method of choice, even direct thrombin inhibitors or factor Xa antagonists would be available. An advantage of INR self-management is the control of drug adherence, which could be an unresolved problem for new anticoagulants.